Uneven effects of trans-vaginal mesh reconstruction on the viscoelastic property of the urinary bladder in patients with pelvic organ prolapse - Lau, Hui-Hsuan; Lai, Cheng-Yuan; Hsieh, Ming-Chun; Peng, Hsien-Yu; Chou, Dylan; Su, Tsung-Hsien; Lee, Jie-Jen; Lin, Tzer-Bin (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThe pathophysiology underlying deficits in bladder storage and possible rationale for how transvaginal mesh (TVM) reconstruction benefits bladder function in patients with pelvic organ prolapse (POP) remain unclear. Compliance, a viscoelastic parameter, crucially characterizes the bladder’s storage function. Pressure-volume analysis (PVA) has been recently applied to specifically assess compliance dynamics during different stages of bladder filling. This study investigated compliance dynamics in patients with POP using PVA and analyzed the impact of TVM on bladder compliance.MethodsPVAs were retrospectively constructed by plotting intravesical volume (Vive) against detrusor pressure (Pdet) in patients with POP undergoing TVM repair. Parameters analyzed included mean compliance during the entire, early, and late halves of bladder filling (Cm, C1/2, and C2/2, respectively); infused volume (Vinf); threshold pressure (Pthd); Pdet changes in the early and late filling (ΔPthd1/2 and ΔPthd2/2, respectively); post-void residual volume (Vres); and ultrasound imaging.ResultsBefore TVM, patients exhibited significantly lower C2/2 than C1/2 (p < 0.001, N = 22), while postoperatively, no significant difference was observed between C2/2 and C1/2 (p = 0.102, N = 22). TVM significantly increased Cm (p = 0.004, N = 22) and C2/2 (p < 0.001, N = 22) but had no significant effect on C1/2 (p = 0.572, N = 22). Postoperatively, Pthd (p = 0.001, N = 22) and ΔPthd2/2 (p = 0.001, N = 22) were significantly reduced, while ΔPthd1/2 (p = 0.084, N = 22) and Vinf (p = 0.112, N = 22) remained unaffected. Ultrasound imaging demonstrated that TVM relieved restrictions on bladder expansion during late filling.DiscussionPatients with POP showed heterogeneous compliance deficits, particularly during late bladder filling. TVM selectively improved compliance impairment possibly by restoring anatomical geometry for bladder expansion.Clinical Trial RegistrationClinicalTrials.gov (NCT05682989).